The Influence of Provincial Minimum Wages and Population On the Open Unemployment Rate of West Java Province - Rizki Hasbianur, Romy; Agustin, Afiqoh; Sukardi, Didi (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
The purpose of this study is to determine the effect of the Provincial Minimum Wage and Population on the Open Unemployment Rate in West Java Province in 2014 - 2023. The research method used is a quantitative method with secondary data obtained from the Central Statistics Agency. The analysis technique used is multiple linear regression analysis with Eviews 12 software. The results of the study prove that partially the Provincial Minimum Wage variable has a positive and significant effect on the Open Unemployment Rate in West Java Province. This is evidenced by the results of the t-test (partial) which has a t-statistic value of 4.100 > t-table 2.365, with a probability value of 0.0046 < 0.05. While the Population variable partially has a negative and significant effect on the Open Unemployment Rate in West Java Province. This is evidenced by the results of the t-test (partial) which has a t- statistic value of -4.246 < t-table 2.365, with a probability value of 0.0038 < 0.05. Simultaneously, the Provincial Minimum Wage and Population variables have a positive and significant effect on the Open Unemployment Rate in West Java Province. This is proven by the results of the F test which has an F-statistic value of 9.053294 > F-table 4.74, with a probability value of 0.011444 < 0.05. Then the results of the determination test (Adjusted R-squared) in this study obtained a value of 64.1% which means it has a fairly strong influence and the remaining 35.9% is determined by factors or variables other than those in this study